Specific Differences in AMELX and AMELY Genes from Sumatran Tigers, Panthera tigris sumatrae (Felidae), for Molecular Sex Identification - Asrori , I.; Tjong, D. H.; Novarino, W.; Roesma, D. I. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
Sex determination by DNA-based molecular techniques in Sumatran tigers needs to be investigated and developed for forensic and population genetic purposes. The amelogenin gene is a marker commonly used for sex determination. In some species, the difference between the AMELX and AMELY sequences has been reported to be in the intron region. However, the difference between the AMELX and AMELY sequences in the Sumatran tiger is unknown. Therefore, it is necessary to investigate the sequence differences in introns between AMELX and AMELY Sumatran tigers to determine the specific differences between male and female samples. This study aimed to analyse the sequence of nucleotide bases in the Sumatran tiger amelogenin gene introns based on the nucleotide base sequences in the amelogenin gene introns. The method in this research is descriptive, with a molecular observation of the AMELX and AMELY Sumatran tiger sequences. The amplified samples were sequenced, and it was found that the lengths of the AMELX and AMELY Sumatran tiger sequences were 215 bp and 194 bp, respectively, with a 21 bp deletion in the AMELY sequence.